Testing a general hypothesis in empirical research using Dm-index - Dominguez-Lara, Sergio (2018)
The Dm-index have many applications in psychometrics, specifically as a item´s construct validity measure. In this paper, we expose an alternative application of index-Dm to testing general hypothesis in empirical research when it includes a general construct, and isn´t possible to have a global score to make this testing. For this purpose, is considered the information of every specific hypothesis testing, and systematize it on Dm. This work offers examples for the correlation and group comparison procedures, obtaining sounds results. Then, the application of Dm in context of general hypothesis testing is promissory.